An integrative approach to the effect of interleukin-6 on adaptation to restraint stress in rats - Viljoen, Monet (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Physiological Sciences))--University of Stellenbosch, 2009.